2000
DOI: 10.1099/0022-1317-81-12-3115
|View full text |Cite
|
Sign up to set email alerts
|

Early accumulation of PrPSc in gut-associated lymphoid and nervous tissues of susceptible sheep from a Romanov flock with natural scrapie

Abstract: The immune system is known to be involved in the early phase of scrapie pathogenesis. However, the infection route of naturally occurring scrapie and its spread within the host are not entirely known. In this study, the pathogenesis of scrapie was investigated in sheep of three PrP genotypes, from 2 to 9 months of age, which were born and raised together in a naturally scrapie-affected Romanov flock. The kinetics of PrP Sc accumulation in sheep organs were determined by immunohistochemistry. PrP Sc was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
359
3
9

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(398 citation statements)
references
References 51 publications
27
359
3
9
Order By: Relevance
“…In natural and experimental diseases, the Wrst neural tissues in which PrP Sc can be highlighted both in sheep and mice scrapie, cattle bovine spongiform encephalopathy (BSE) and deer chronic wasting disease (CWD) is the enteric nervous system (ENS) of the gut (Andreoletti et al 2000;van Keulen et al 2000;Sigurdson et al 2001;Iwata et al 2006). This intramural nervous system is composed of two networks, the submucosal and the myenteric plexi, which contain the neuronal cell bodies and their processes.…”
Section: Introductionmentioning
confidence: 99%
“…In natural and experimental diseases, the Wrst neural tissues in which PrP Sc can be highlighted both in sheep and mice scrapie, cattle bovine spongiform encephalopathy (BSE) and deer chronic wasting disease (CWD) is the enteric nervous system (ENS) of the gut (Andreoletti et al 2000;van Keulen et al 2000;Sigurdson et al 2001;Iwata et al 2006). This intramural nervous system is composed of two networks, the submucosal and the myenteric plexi, which contain the neuronal cell bodies and their processes.…”
Section: Introductionmentioning
confidence: 99%
“…Except in mice, prionin proteins are comprised of four or five equally spaced β-sheets and it has been proposed that these interact with PrP C and participate in their conversion to PrP Sc 3 . It is also reported that expression of prionins in subjects results in the expression of specific anti-prionin endogenous antibodies and Altegen Inc. have exploited this to develop a blood-based TSE ELISA test to detect anti-prionin antibodies 3,4 . It is claimed that the Altegen test is able to detect endogenous anti-bovine, anti-scrapie and anti-CJD prionin antibodies in as little as 1-2 µL serum and results are obtained within 3 h. The test reportedly indicates TSE infection 2-3 years post infection and is highly sensitive and specific in all premortem subjects.…”
Section: Prioninmentioning
confidence: 99%
“…The spread of PrP Sc to the lymphoid organs is thought to be mediated by the lymphoreticular system. Studies have shown that the eventual transport of PrP Sc to the CNS is mediated by axonal transport within the parasympathetic and the sympathetic nervous system [4,62,63,109,115,116].…”
Section: Introductionmentioning
confidence: 99%
“…The sequential detection of abnormal prion protein in lymphoreticular tissue and along neural projections to the CNS after peripheral infection in various animal models led to the conclusion that these tissues are involved in the spread of the TSE agent to the CNS [3,7,17,28,35,44,46]. The sciatic nerve is a useful structure for monitoring the centripetal neural spread of the scrapie agent [29] and rapid disease onset was observed after intrasciatic injections of strains of transmissible mink encephalopathy (TME) in rodents [4].…”
Section: Introductionmentioning
confidence: 99%